Emotional Exhaustion Scale: factorial structure and the validity of the items in students of a private university - Dominguez Lara, Sergio Alexis (2014)
Objective: Analyze the psychometric properties of the Emotional Exhaustion Scale. Method: Design ex post facto retrospective and instrumental. Were evaluated 448 college students of Psychology of a private university of Lima, 128 males and 320 women, with ages between 15 and 48 years (M=21.09). Was used the Emotional Exhaustion Scale, Stait-Trait Anxiety Inventory, Stait-Trait Depression Inventory, Psychometric properties of self-efficacy for academic situations scale and Test Anxiety Inventory. Results: Factor analysis confirmed the unidimensional structure (appropriate fit indexes) and was found Dm Index adequate, realizing construct validity. With regard to reliability, Cronbach’s alpha coefficient is suitable. Conclusion: The EES has adequate psychometric properties to be applied to college students, supporting its use as a test of evaluation of emotional exhaustion. Scope and limitations are discussed.